Analysis of the β-Tubulin Genes from Enterocytozoon bieneusi Isolates from a Human and Rhesus Macaque - Akiyoshi, Donna E. (2007)
Enterocytozoon bieneusi is the most common and clinically significant microsporidium associated with chronic diarrhea and wasting in immunocompromised humans. Albendazole, which is effective against several helminths, protozoa, and microsporidia, is relatively ineffective against infections due to E. bieneusi. A likely explanation for the observed clinical resistance to albendazole was discovered from sequence analysis of the E. bieneusi β-tubulin from isolates from an infected human and a naturally infected rhesus macaque. The β-tubulin of E. bieneusi has a substitution at Glu(198), which is one of six amino acids reported to be associated with benzimidazole sensitivity.